(3GdeeJY aj TQM GdebfYs - (3GdpepQrZJj , eMeO Hf SYjO Hf eMeO Hf jMji GdShSj, CHh YHO Gddg,J (B1089 (3g` s ((3GdWjH Hf eMeO Hf eMeO Hf GdMSf GdRjGJ GdMSjfi s)
(3ChdgG (B:s
(3bGd GdMeO ddg GdPi ef YdjfG jSGQI Yde ChbGJ Gddjd hGdfgGQ hHYO , ajbhd gPG TQM bUOfG Hg JHjjf GdeSei HGdebfY ai Yde CHj ebQY s
(3BNQgG (B:s
(3hbhdg (B: (3eUdjkG MGd ef GdJGA ai bhdg Ci SejJg MGdI chfi eUdjkG cGf GdaQGZ ef gPG GdTQM s
(3Vef eLehY , JQJjHgG (B: (3ef U (B77 - (3U(B121s
(3HgG LOGhds
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B139 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B38s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B615 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B707 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs